Psychometric Properties of the Persian Translation of Video Gaming Addiction Test - Zahrasadat Hosseini; Roya Delpazirian; Hosseini Mohajeri; Peyman Hassani Abharian (Basic and Clinical Neuroscience, 2019)
Introduction: The current study aims to measure the validity, reliability, and psychometric properties of the Persian translation of the Video Gaming Addiction Test (VAT). Methods: A total of 280 young men (14-20 years old) (Mean±SD age: 17.22±1.8 years), including excessive gamers and normal subjects, entered the study. They answered VAT, Visual Analog Scale (VAS), and Conner-Davidson Resilience Scale (CD-RISC). The VAT was translated and then back-translated. For testing reliability, we used the Cronbach alpha, split-half method, and Guttman method. Also, convergent and discriminant validity were tested to examine the construct validity of the translated version of VAT. Results: The Cronbach alpha for the total scale was 0.81. Also, after splitting questions in half, the Cronbach alpha values for these halves were 0.71 and 0.69. Six Guttman lambdas were calculated with 0.75 minimum and 0.82 maximum, all showing good reliability of the test. Convergent validity was tested by testing the correlation between VAT and VAS. The Pearson correlation was fond 0.73, showing a strong relationship between the two factors (P<0.001). For testing discriminant validity, the association of VAT with CD-RISC was tested, showing no correlation between these scales (r=-0.157; P=0.09). Conclusion: The Persian translation of the VAT is valid and reliable, and it is appropriate for research and clinical use with acceptable properties, similar to the original version.